2013
DOI: 10.1007/s00382-013-1922-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate model benchmarking with glacial and mid-Holocene climates

Abstract: Past climates provide a test of models' ability to predict climate change. We present a comprehensive evaluation of state-of-the-art models against Last Glacial Maximum and mid-Holocene climates, using reconstructions of land and ocean climates and simulations from the Palaeoclimate Modelling and Coupled Modelling Intercomparison Projects. Newer models do not perform better than earlier versions despite higher resolution and complexity. Differences in climate sensitivity only weakly account for differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
236
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(256 citation statements)
references
References 48 publications
20
236
0
Order By: Relevance
“…7). A somewhat limited cooling over southern Europe is also shown in the model ensemble, but in this case it can be attributed to the decrease in winter insolation across the mid-and lower latitudes of the Northern Hemisphere at this time which results in a general cooling over these areas in most model simulations (Davis and Brewer, 2009;Harrison et al, 2013). Reconstructed precipitation anomalies are also consistent with a positive AO/NAO, showing wetter conditions over northern Europe and drier conditions over southern Europe.…”
Section: Wintermentioning
confidence: 56%
See 1 more Smart Citation
“…7). A somewhat limited cooling over southern Europe is also shown in the model ensemble, but in this case it can be attributed to the decrease in winter insolation across the mid-and lower latitudes of the Northern Hemisphere at this time which results in a general cooling over these areas in most model simulations (Davis and Brewer, 2009;Harrison et al, 2013). Reconstructed precipitation anomalies are also consistent with a positive AO/NAO, showing wetter conditions over northern Europe and drier conditions over southern Europe.…”
Section: Wintermentioning
confidence: 56%
“…8). At the Northern Hemisphere scale, the slight warming over the far north of Europe in the ensemble is part of a strong warming response over the Barents Sea, whilst a slight cooling to the south reflects a more general cooling over lower mid-and tropical latitudes, both of which are typical of PMIP3/CMIP5 and earlier models Harrison et al, 2013). Neither the ensemble nor individual PMIP3/CMIP5 models show the pattern of winter temperature anomalies shown by the reconstruction, which indicates a more extensive and relatively strong warming extending over much of northern and central Europe, together with a strong but somewhat less extensive cooling over southern Europe.…”
Section: Wintermentioning
confidence: 85%
“…Benchmarking using modern observations does not provide an assessment of whether model performance is likely to be realistic under radically different climate conditions. The climate-modelling community use records of the preobservational era to assess how well models simulate climates significantly different from the present (Braconnot et al, 2012;Flato et al, 2014;Harrison et al, 2014Harrison et al, , 2015Schmidt et al, 2014). FireMIP will extend this approach to the evaluation of fire-enabled vegetation models, building on the work of BrĂŒcher et al (2014).…”
Section: Carbon Combustibilitymentioning
confidence: 99%
“…In CMIP5/PMIP3, most models have been upgraded from atmosphere-ocean coupled model (AOGCM) to the Earth System Models (ESM), containing more complex processes than those in PMIP2 models. Harrison et al (2014) compared PMIP2 and CMIP5/ PMIP3 simulations with the reconstructions and found that some models perform better than others. It suggests a careful evaluation of individual model and the Multi-Model Ensemble (MME) are necessary in analyzing the model results.…”
Section: Introductionmentioning
confidence: 99%